Accelerating Alloy Development for Additive Manufacturing - Kammermeier, Elisabeth; Weidinger, Julius; Ionov, Illya; Ramsperger, Markus; Wahlmann, Benjamin; Körner, Carolin; Zenk, Christopher (Minerals, Metals and Materials Series, 2024)
Additive manufacturing (AM) is revolutionizing the production of complex superalloy parts, yet its advancement is hindered by the high costs and extensive time required for atomizing powders from which new alloys are produced and tested. This study presents our approach to expedite and economize alloy development for AM. At the heart of this method is the CALPHAD calculation of phase Diagrams (CALPHAD)-based multi-criteria optimization algorithm PyMultOpt, utilized for selecting potential alloys, which are then produced through arc-melting. Our innovative testing framework involves two key processes: (i) assessing alloy processability via electron beam remelting of bulk material, and (ii) evaluating mechanical properties after refining coarse-grained material via deformation and recrystallization. Focusing on Alloy 247 and derivatives selected through PyMultOpt, our approach successfully emulates AM-like microstructures in arc-melted material. The compressive creep tests on the recrystallized microstructure of Alloy 247 indicate a minimal creep rate comparable to that of AM specimens. Moreover, profilometry-based indentation plastometry tests at 760 °C offer a rapid, high-temperature evaluation method, allowing for preliminary alloy ranking before extensive creep testing. This study demonstrates that remelting and recrystallization of bulk material can reproduce AM-like microstructures, enabling a faster and more cost-effective assessment and ranking of new alloys in terms of their mechanical properties and AM-processability, as opposed to the traditional, powder-dependent alloy development methods.
CRIS-Team Scopus Importer:2024-09-06
Keywords: Additive Manufacturing; Alloy 247; Alloy development; PyMultOpt; Recrystallization